A flexible curriculum for computer science undergraduate major - Manacero A., Jr [UNESP]; Dos Santos, R. R. [UNESP]; Marranghello, N. [UNESP]; Pereira, A. S. [UNESP]; Cansian, A. M. [UNESP]; Ralha, J. C L [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This paper describes an innovative approach to establish a CS curriculum, aiming flexibility and minimization of the time spent in the classrooms. This approach has been developed at the Paulista State University - Unesp - at São José do Rio Preto, and is producing very interesting results. The load reduction is achieved through a series of fundamental core and breadth courses that precede depth courses in specific areas. The flexibility comes as a side effect of the depth courses, which can be adapted without any changes in the core courses. In the following pages we fully describe our motivations, actions and results.
Keywords: Computer science curriculum; Flexible curricula; Computer science; Curricula; Societies and institutions; Students; Technology; Flexible curriculum; Engineering education